2020
DOI: 10.1016/j.polymer.2020.122734
|View full text |Cite
|
Sign up to set email alerts
|

Competition between nucleation and confinement in the crystallization of poly(ethylene glycol)/ large aspect ratio hectorite nanocomposites

Abstract: Optical Microscopy (PLOM). DSC results reveal a competition between the nucleating effect of Hec, which was particularly important at low amounts, and the PEG confinement effect at higher filler loadings. Applying a self-nucleation protocol, the nucleation efficiency of the hectorite was shown to be up to 67%. The isothermal crystallization kinetics accelerated at low Hec contents (nucleation), went through a maximum and then decreased (confinement) as Hec content increased. Additionaly, a clear correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Previous studies have reported intercalated phases of layered silicates with PEG volume contents of 46 vol % 34 36 , 43 , 44 and 30 vol % 36 corresponding to periodicities of 1.8 and 1.4 nm, respectively. The present observed periodicities (1.77 and 1.38 nm for Hec/2PEG and Hec/1PEG, respectively; Figure 2 , bottom) agree well with the published values.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have reported intercalated phases of layered silicates with PEG volume contents of 46 vol % 34 36 , 43 , 44 and 30 vol % 36 corresponding to periodicities of 1.8 and 1.4 nm, respectively. The present observed periodicities (1.77 and 1.38 nm for Hec/2PEG and Hec/1PEG, respectively; Figure 2 , bottom) agree well with the published values.…”
Section: Resultsmentioning
confidence: 98%
“…The overall isothermal crystallization behavior was probed by the DSC measurements in which both primary nucleation and crystal growth are considered [ 56 , 57 ]. Avrami equation was employed to understand the primary crystallization process.…”
Section: Resultsmentioning
confidence: 99%
“…This is even more critical in the case of layered additives, in which the interactions not only affect the dispersion of the additive within the polymer matrix, but they define the final nanohybrid structure as well. In such cases, three different structures can be obtained depending on the interactions [ 33 , 34 ]: (i) the phase separated, when the interactions between the chains and the fillers are unfavorable, which results in each component residing in its own phase; (ii) the intercalated one [ 17 , 28 , 29 , 35 , 36 , 37 ], where the polymer can diffuse between the layers of the additive, creating a structure of alternating soft–hard components, each one of nm-thickness, and (iii) the exfoliated one [ 38 , 39 , 40 , 41 , 42 , 43 ], where the favorable interactions lead to the destruction of the layered structure of the inorganic material and to the dispersion of individual platelets within the polymer. Both intercalated and exfoliated structures offer certain advantages: the former shows enhanced mechanical properties, while for hybrids with low polymer content, it offers the ability to investigate polymer structure, dynamics and properties under severe confinement, whereas the latter provides optimized properties due to the percolated network formed from the dispersion of the additive platelets [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%